Sprint running mechanics are associated with hamstring strain injury: a 6-month prospective cohort study of 126 elite male footballers - Bramah, C.; Rhodes, S.; Clarke-Cornwell, A.; Dos`Santos, T. (British Journal of Sports Medicine, 2025)
Objective To investigate the association between sprint running biomechanics and sprint-related hamstring strain injury (HSI) in elite male football players.